Spin Compensation Temperatures in the Mean-field Theory of a Mixed Spin-3/2 and Spin-7/2 Blume-Capel Ising Model - Hadey K. Mohamad (Journal of Global Pharma Technology, 2016)
In this research it has been constructed the ground-state phase diagram of a mixed spin-3/2 and spin-7/2 Blume-Capel Ising system on a square lattice in theplane. Magnetic phase transitions, in a molecular based magnet, are tested using mean field method (MFM). The equilibrium magnetizations can be achieved by minimizing the free energy which is vital for locating and spin compensation points as well. By utilizing mean field theory (MFT) on principles of Bogoliubov inequality of the free energy, it has been investigated the spin compensation phenomena. In particular, characteristic ferrimagnetic features have been shown depending on the negative values of the different single-ion anisotropies, acting on the atoms and atoms, respectively.Keywords: Blume-Capel Ising model; Ground-state phase diagram; Compensation temperature; Magnetic free energy.